The transporting and transformative power of love in the narratives of Aitmatov - Korkmaz, Ramazan (Ahmet Yesevi Univ, 2008)
In Aitmatov's narratives love is a lofty value that can overcome all distances, improve man's spiritual nature and bring people closer together. The power of love, which can transcend all differences, appears in his fiction as a constructive phenomenon that transforms man's nature radically, endowing him with the ability to become a part of the rhythm of the universe. Love forces man to look inside and listen to his heart, which in turn allows him to discover his inner freedom. Aitmatov, however, does not regard love as a feeling reserved for humankind only. To him, love is a universal expansion of one's existence. Aitmatov, who represents this non-human and unaesthetic side of love through animals like the camel, the wolf, and the horse, always foregrounds the constructive and transformative function of love in his works.
Aytmatov anlatılarında aşkın eriştirici ve dönüştürücü gücü
Keywords: Chingiz Aitmatov; love; existence; freedom